PERAN KUD ARGOPURO SEBAGAI STABILISATOR PEREKONOMIAN MASYARAKAT KRUCIL PASCA COVID-19 - Ikhsan, Moh. Taufik Khoiril; Septiandika, Verto (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2021)
The problem discussed in this study is how the Krucil village community overcomes the post-covid-19 economic instability through the role of KUD Argopuro. The purpose of this research is to find out how big the impact of the role of KUD Argopuro in stabilizing the economy of the Krucil village community after COVID-19. The subjects in this study were the managers and administrators of the KUD Argopuro, as well as the community who played an active role in the activities of the KUD Arogpuro. This research method uses qualitative research methods or case research methods. Data collection in the study includes interviews, appropriate reference books and direct observations from the field. The data generated in this study is not in digital form, but in the form of narratives, descriptions, stories, written and unwritten documents. The results of the research are expected to help rural communities in other areas to stabilize or improve the quality of the rural economy after the COVID-19 pandemic, such as the effective program that has been successfully carried out in increasing existing human resources by KUD Argopuro as a relevant reference source.